Methanol‐induced change of the mechanism of the temperature‐ and pressure‐induced collapse of N‐Substituted acrylamide copolymers. Issue 7 (7th February 2015) - Hofmann, Christian H.; Grobelny, Sebastian; Panek, Paweł T.; Heinen, Laura K. M.; Wiegand, Ann‐Kristin; Plamper, Felix A.; Jacob, Christoph R.; Winter, Roland; Richtering, Walter
ABSTRACT The solvation of two differently composed linear statistical copolymers from N, N‐diethyl acrylamide (DEAm) and N‐isopropyl acrylamide is studied by Fourier‐transform infrared spectroscopy. The solvent is changed from pure water to mixtures with methanol to investigate the cononsolvency effect. Furthermore, the influence of temperature and pressure is studied. The IR results are interpreted by sub‐band fitting of the amide I' band and quantum–chemical calculations. There are significant differences between the two copolymers that cannot be explained by a weighted superposition of the homopolymer spectra. An excess of DEAm units leads to a high number of nonsolvated side chains already in pure water. This high number is reached for equimolar copolymers only when methanol is added. The mechanism of the temperature‐ or pressure‐induced phase transition changes upon methanol addition for both copolymers. Generally, the phenomena are deduced to cooperativity at equimolar composition that is perturbed by methanol. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 532–544